The Impact of Gender on Unemployment: Cross‑country and Within‑country Analysis of the European Labour Markets during Economic Recession - Medková, Tatiana (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
This paper investigates the impact of gender on the individual probability of being unemployed and makes a cross‑country comparison across 13 European countries during the European recession. Applying a general logit model for each country and capital, whilst controlling for the year, as well as for individual and regional characteristics, the probability of unemployment was estimated using individual labour force data from 2011 to 2014. Cook’s distance is used to examine the differences between labour markets of capital regions (or cities) and non‑capital regions. Using the size of Cook’s distance, models are calibrated, and models which include the degree of urbanization and occupation type are evaluated. The results are presented in the form of a spatial map and show that gender affects the probability of unemployment in the majority of the analysed countries. Overall, the effect is lower in capital than in non‑capital regions.